If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-4=9x+52
We move all terms to the left:
2x-4-(9x+52)=0
We get rid of parentheses
2x-9x-52-4=0
We add all the numbers together, and all the variables
-7x-56=0
We move all terms containing x to the left, all other terms to the right
-7x=56
x=56/-7
x=-8
| 3x+2(2x)=133 | | 6m-4=+11 | | 3x+14.5=32.5 | | 6(5t-9)=36 | | 3p+14.5=53.5 | | 4-5x=26-x | | 6m-7=4m | | 18*k=30 | | R~2=r+18 | | 20+(-1)x=0 | | 40+(-1d)=5 | | 40+(-1d)=10 | | -8x=78-2 | | 1/4y-3=-13 | | 3213e+124e=1e | | 0=0.75x+5 | | 6x+36=2x+12 | | 2v-6=-3(v-8) | | 3(x+2)^2=15 | | 9(v+3)=3v+45 | | X+14=5x+38 | | 9p^2-29=-5 | | 9v-1=-7(v-9) | | 7910-4x)=70 | | 3+12a=75 | | 0=-16t^2-120t-50 | | 4x+5+7x-2=180 | | 3+12a=63 | | 3x+8=9-10x | | 79x+31=90 | | 79x+31=30 | | 3(x+2)=6x+24 |